1987
DOI: 10.1071/pp9870669
|View full text |Cite
|
Sign up to set email alerts
|

Proline Analogues in Melaleuca Species: Response of Melaleuca lanceolata and M. uncinata to Water Stress and Salinity

Abstract: Fifteen species of Melaleuca and two species of Callistemon from the field were examined to determine whether they accumulated nitrogen-containing compatible solutes and, if so, which. In addition to L-proline, N-methyl-L-proline (MP) (isolated for the first time from plants), trans-4-hydroxy-N-methyl- L-proline (MHP), and N, N'-dimethyl-trans-4-hydroxy-L-proline (DHP) were found in various combinations in the 15 Melaleuca species. M. lanceolata seedlings were subjected to water or salinity stress and M. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
2

Year Published

1990
1990
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 0 publications
0
14
2
Order By: Relevance
“…various betaines in Melaleuca spp. ; Naidu et al . 1987, 2000), we found no such evidence for the species studied here.…”
Section: Discussionmentioning
confidence: 99%
“…various betaines in Melaleuca spp. ; Naidu et al . 1987, 2000), we found no such evidence for the species studied here.…”
Section: Discussionmentioning
confidence: 99%
“…Determination of the levels ofthe putative intermediates involved in the synthesis ofthese imino acid betaines (e.g. N-methylproline, N-methylpipecolic acid, and N-methylhydroxyproline) (11), and their rates of labeling from supplied isotopically labeled amino acid precursors are now required to elucidate these pathways. Presumably, the pathway ofhydroxyprolinebetaine synthesis in alfalfa could be explored by supplying isotopically labeled proline, hydroxyproline, N-methylproline, and N-methylhydroxyproline to high-and low-hydroxyprolinebetaine genotypes to determine if hydroxyprolinebetaine deficiency results from a lesion in the capacity to metabolize hydroxyproline to N-methyhydroxyproline, a lesion in the capacity to metabolize N-methylhydroxyproline to hydroxyprolinebetaine, and/or a lesion in the capacity to metabolize N-methylproline to Nmethylhydroxyproline.…”
Section: Resultsmentioning
confidence: 99%
“…For ion compartmentation to take place, osmotic balance must be achieved between the vacuole and cytoplasm, which can occur through the production of compatible organic solutes in the cytosol and organelles (Hall et al ., 1978). The compatible organic solute methyl proline has been found in leaves of M. cuticularis in the field (Naidu et al ., 1987, 2000; Poljakoff‐Mayber et al ., 1987; Carter, 2004), but in these studies the concentration was not found to increase with drought or osmotic stress. Similarly, proline was measured in the cladodes (modified photosynthetic stems) of C. obesa in the field, but despite marked seasonal changes in root‐zone salinity the concentrations were relatively constant (Carter, 2004).…”
Section: Introductionmentioning
confidence: 99%